The Effect Of Asset Growth And Debt To Equity Ratio (DER) On Price To Book Value (PBV) - Putri; Muhammad Ilham Wardhana; Andi Mustika Amin; Abdul Rahman; Annisa Paramaswary Aslam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Manufacturing companies play an important role in Indonesia’s economy, and this sector comprises several subsectors, one of which is the miscellaneous industry sector. The miscellaneous industry sector is important because it is considered a national priority industry with development potential and also attracts investors. However, during the 2020–2024 period, the sector experienced a decline in asset growth alongside a decrease in market valuation. These conditions motivated this study, which aims to examine the effect of company growth and capital structure on company value, both partially and simultaneously, in manufacturing companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange during the 2020-2024 period. This study uses a causal associative quantitative approach with the Statistical Package for Social Sciences (SPSS) method, and samples are determined using the Purposive Sampling technique on companies that meet the research criteria. The research results indicate that asset growth (TAG) and capital structure (DER) do not have a significant effect on firm value (PBV), both partially and simultaneously. The coefficient of determination (R2) value of 0,009 shows that only 0,9% of the variation in firm value can be explained by these two variables, while 90,1% is influenced by other factors outside the study, such as profitability, company size, and capital market conditions. Thus, the findings indicate that asset growth and capital structure are not dominant determinants of firm value within the diversified industrial sector on the IDX during the 2020–2024 period. These results reinforce the view that other fundamental factors, such as operational efficiency, profitability, and investor confidence, play a greater role in shaping a company's market value.